2019
DOI: 10.3390/antiox8060190
|View full text |Cite
|
Sign up to set email alerts
|

Marine Alga Ecklonia cava Extract and Dieckol Attenuate Prostaglandin E2 Production in HaCaT Keratinocytes Exposed to Airborne Particulate Matter

Abstract: Atmospheric particulate matter (PM) is an important cause of skin damage, and an increasing number of studies have been conducted to discover safe, natural materials that can alleviate the oxidative stress and inflammation caused by PM. It has been previously shown that the extract of Ecklonia cava Kjellman, a perennial brown macroalga, can alleviate oxidative stress in epidermal keratinocytes exposed to PM less than 10 microns in diameter (PM10). The present study was undertaken to further examine the anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 62 publications
1
40
0
Order By: Relevance
“…E. cava conversely, is known to have anti-inflammatory efficacy in various conditions [23,24]. A recent study demonstrated anti-inflammatory effects of E. cava against airborne particulate matter (PM), as it was able to suppress PM-induced COX and PGE 2 production in keratinocytes [24]. We also confirmed that E. cava exerts inhibitory effects on LPS-induced NO production and IL-4-induced eotaxin-1/CCL11 ( Figure A1).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…E. cava conversely, is known to have anti-inflammatory efficacy in various conditions [23,24]. A recent study demonstrated anti-inflammatory effects of E. cava against airborne particulate matter (PM), as it was able to suppress PM-induced COX and PGE 2 production in keratinocytes [24]. We also confirmed that E. cava exerts inhibitory effects on LPS-induced NO production and IL-4-induced eotaxin-1/CCL11 ( Figure A1).…”
Section: Discussionsupporting
confidence: 76%
“…Urban dust has been reported to cause skin inflammation through upregulation of inflammatory mediators such as ROS, COX, PGE 2 and TNF-α. E. cava conversely, is known to have anti-inflammatory efficacy in various conditions [23,24]. A recent study demonstrated anti-inflammatory effects of E. cava against airborne particulate matter (PM), as it was able to suppress PM-induced COX and PGE 2 production in keratinocytes [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the penetration of PM depending on size and agglomeration into the epidermis in healthy and diseased skin must be evaluated in future studies. In 3D HSE models, a systemic treatment with PM (200 μg/mL) induced alterations in skin morphology and expression levels of structural proteins after a long time exposure (i.e., 48 h up to 6 days) [125,126]. In 3D HEE models, PM usually in concentrations of up to 50 μg/mL was mainly applied topically and short-term exposures (i.e., 24 to 48 h) were performed [128,130,132,133].…”
Section: Physical Barriermentioning
confidence: 99%
“…The PM-induced activation of NF-κB leads to the increased transcription of its target genes and their protein expressions such as IL-1α, IL-1β, IL-6, IL-8, ICAM1, COX2 and TNF-α [124,128,130,133,135,138,139,142,169,173,181,227,229,230,243]. PM-induced COX2 expression leads to induced production of PGE 2 [122,126,137,143,179,181,231,232].…”
Section: Pm-induced Activation Of Nf-κbmentioning
confidence: 99%
“…Carrageenan has been widely used as a tool in the screening of novel antiinflammatory drugs [364]. Among others, Porphyra vietnamensis [365,366], Eucheuma Cottonii [367], Dichotomaria obtusata ( Figure 17) [368], Cystoseira sedoides, Cladostephus spongiosis, Padina pavonica ( Figure 18) [369], Ecklonia cava (due to phlorotannins) [370][371][372], Caulerpa racemose [373], Sarcodia ceylanica [374], actinotrichia fragilis [375], Dictyota menstrualis ( Figure 19) [376], Gracilaria cornea [377], Gracilaria birdiae [378], Class Phaeophyceae, Rhodophyceae and Chlorophyceae [379], Caulerpa curpressoides [380,381], Ulva lactuca ( Figure 20) [382], Sargassum wightii and Halophila ovalis [383], Grateloupia lanceolate [384], Sargassum fulvellum and Sargassum thunbergii [385], Briareum excavatum [386], Caulerpa racemose [387], Sargassum hemiphyllum [388], Laurencia obtusa [389], Caulerpa kempfii [390] Caulerpa cupressoides [391] are reported for their analgesic and anti-inflammatory properties.…”
Section: Analgesic and Anti-inflammatory Potentialmentioning
confidence: 99%